2017
DOI: 10.3892/mmr.2017.8149
|View full text |Cite
|
Sign up to set email alerts
|

Genes and pathways associated with the occurrence of malignancy in benign lymphoepithelial lesions

Abstract: There is increasing evidence concerning the occurrence of malignant lymphoma among people suffering from Mikulicz disease, also termed benign lymphoepithelial lesion (BLEL) and immunoglobulin G4-associated disease. However, the underlying molecular mechanism of the malignant transformation remains unclear. The present study aimed to investigate the gene expression profile between BLEL and malignant lymphoepithelial lesion (MLEL) conditions using tissue microarray analysis, to identify genes and pathways which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Ohno ( 13 ) et al believe that IgG4+ marginal zone lymphoma is characterized by the up-regulation of Th2 and regulatory cytokines, and which is similar to IgG4-RD, but different from IgG4− marginal zone lymphoma, suggesting that the pathogenesis of IgG4+ lymphoma might be different from IgG4− lymphoma. Adzavon ( 14 ) et al preliminarily detected differentially expressed genes and pathways in IgG4-related dacryoadenitis and lymphoma using gene expression profile microarray analysis, which mainly focused on the B cell receptor signaling pathway, the NF-κB signaling pathway, FcγR mediated phagocytosis, the FcεRI signaling pathway, the EB virus infection signaling pathway, and the cancer signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ohno ( 13 ) et al believe that IgG4+ marginal zone lymphoma is characterized by the up-regulation of Th2 and regulatory cytokines, and which is similar to IgG4-RD, but different from IgG4− marginal zone lymphoma, suggesting that the pathogenesis of IgG4+ lymphoma might be different from IgG4− lymphoma. Adzavon ( 14 ) et al preliminarily detected differentially expressed genes and pathways in IgG4-related dacryoadenitis and lymphoma using gene expression profile microarray analysis, which mainly focused on the B cell receptor signaling pathway, the NF-κB signaling pathway, FcγR mediated phagocytosis, the FcεRI signaling pathway, the EB virus infection signaling pathway, and the cancer signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…LGBLEL is a chronic inflammatory disease, which clinical studies have indicated may be related to diseases including sinusitis and allergic rhinitis. Adzavon et al 24 found that the FcεRI signaling pathway may be involved in the mechanism that leads to malignant development in LGBLEL. The occurrence of malignant transformation is one of the pathological processes of LGBLEL; therefore, the FcεRI signaling pathway was examined in this study to further verify its role in LGBLEL pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…LGBLEL is a chronic inflammatory disease, which clinical studies have indicated may be related to sinusitis, allergic rhinitis, and other diseases. Adzavon et al [16] found that the FcεRI signaling pathway may be involved in the mechanism leading to malignant development in LGBLEL. The occurrence of malignant transformation was one of the pathological processes of LGBLEL; therefore, the FcεRI signaling pathway was examined in this study to further verify its role in the LGBLEL pathogenesis.…”
Section: Discussionmentioning
confidence: 99%